Genome-wide association study of paliperidone efficacy. Issue 1 (January 2017) - Li, Qingqin; Wineinger, Nathan E.; Fu, Dong-Jing; Libiger, Ondrej; Alphs, Larry; Savitz, Adam; Gopal, Srihari; Cohen, Nadine; Schork, Nicholas J.
Abstract : Objective: Clinical response to the atypical antipsychotic paliperidone is known to vary among schizophrenic patients. We carried out a genome-wide association study to identify common genetic variants predictive of paliperidone efficacy. Methods: We leveraged a collection of 1390 samples from individuals of European ancestry enrolled in 12 clinical studies investigating the efficacy of the extended-release tablet paliperidone ER ( n 1 =490) and the once-monthly injection paliperidone palmitate ( n 2 =550 and n 3 =350). We carried out a genome-wide association study using a general linear model (GLM) analysis on three separate cohorts, followed by meta-analysis and using a mixed linear model analysis on all samples. The variations in response explained by each single nucleotide polymorphism ( h 2 SNP ) were estimated. Results: No SNP passed genome-wide significance in the GLM-based analyses with suggestive signals from rs56240334 [ P =7.97×10 −8 for change in the Clinical Global Impression Scale-Severity (CGI-S); P =8.72×10 −7 for change in the total Positive and Negative Syndrome Scale (PANSS)] in the intron of ADCK1 . The mixed linear model-based association P -values for rs56240334 were consistent with the results from GLM-based analyses and the association with change in CGI-S ( P =4.26×10 −8 ) reached genome-wide significance (i.e. P <5×10 −8 ). We also found suggestive evidence for a polygenic contribution toward paliperidone treatment response with estimates of heritability, h 2 SNP, ranging from 0.31 to 0.43 for change in the total PANSS score, the PANSS positive Marder factor score, and CGI-S. Conclusion: Genetic variations in the ADCK1 gene may differentially predict paliperidone efficacy in schizophrenic patients. However, this finding should be replicated in additional samples. Abstract : Supplemental Digital Content is available in the text.